Identifying the relationship between VOCs emission and temperature/humidity changes in new apartments in the hot desert climate - Jung, Chuloh; Mahmoud, Naglaa Sami Abdelaziz; Alqassimi, Nahla (Frontiers in Built Environment, 2022)
Much previous research in different countries describes a strong dependence on temperature and humidity for indoor air pollutants generated from building materials. Since many types of building materials are complexly applied in residential buildings in UAE and are constantly using air-conditioning, the result might be different from the characteristics of indoor air pollutants from a small chamber experiment. This paper aims to investigate the relationship between the concentration of indoor air pollutants according to changes in temperature and humidity in newly built apartments before moving in. As a methodology, a field measurement was performed in 23 housing units in five different residential towers in Ajman, United Arab Emirates. Before the measurement, a 7-day bake-out was completed, and the target units were measured 30 days before moving in. The result showed that formaldehyde (HCHO) and VOCs such as benzene (C6H6), toluene (C7H8), ethylbenzene (C8H10), xylene (C8H10), and styrene (C8H8) have consistent humidity dependence within the range of 15 %–60% of relative humidity (RH). It was impossible to confirm the temperature dependency since it showed different characteristics for each apartment between 22°C and 33°C. There is a limit to predicting the occurrence of indoor air pollutants in the apartment only with microclimatic factors since there are many other variables, such as various building materials, management history of materials, and construction methods. However, it was proven that there is an emission cut-off point where the generation of indoor air pollutants deviates from a linear relationship in the RH 40%–50% and 25°C. These temperature and humidity ranges are synchronized with daily life ranges.